2007
DOI: 10.1074/jbc.m702547200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Sequestration of Transcription Factor Activity by Repetitive DNA

Abstract: Higher eukaryote genomes contain repetitive DNAs, often concentrated in transcriptionally inactive heterochromatin. Although repetitive DNAs are not typically considered as regulatory elements that directly affect transcription, they can contain binding sites for some transcription factors. Here, we demonstrate that binding of the transcription factor CCAAT/ enhancer-binding protein ␣ (C/EBP␣) to the mouse major ␣-satellite repetitive DNA sequesters C/EBP␣ in the transcriptionally inert pericentromeric heteroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 54 publications
2
48
0
Order By: Relevance
“…Fluorescence recovery after photo bleaching (FRAP), single molecule, in vivo footprinting, and other in vivo measurements of DNA binding generally support these thermodynamic predictions: most indicate that >90% of transcription factors molecules contact DNA (13)(14)(15)(16)(17)(18), although estimates of only ∼25% have been proposed in some FRAP studies (19). The sequence-independent, electrostatic affinity that all transcription factors have for DNA (K d ∼10 −6 M) is sufficient to cause most molecules to be bound to DNA (10,12,15).…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Fluorescence recovery after photo bleaching (FRAP), single molecule, in vivo footprinting, and other in vivo measurements of DNA binding generally support these thermodynamic predictions: most indicate that >90% of transcription factors molecules contact DNA (13)(14)(15)(16)(17)(18), although estimates of only ∼25% have been proposed in some FRAP studies (19). The sequence-independent, electrostatic affinity that all transcription factors have for DNA (K d ∼10 −6 M) is sufficient to cause most molecules to be bound to DNA (10,12,15).…”
mentioning
confidence: 79%
“…It has long been appreciated, however, that low-occupancy interactions that do not affect transcription in cis will affect the system in trans by lowering the concentration of unbound transcription factor molecules, which will in turn necessarily reduce the occupancy levels of transcription factors at highly bound, functional cis-regulatory regions (10)(11)(12)(13)(14)(15)(16)(17)(18). Low-occupancy DNA binding could in this sense be said to be functional, but it is a very different function from that of regulating nearby genes via cis-regulatory regions, and most low-occupancy interactions are not under strong natural selection in the same way that direct regulatory interactions in cis-regulatory regions are (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, polymorphic Y chromosomes might exert their effects on gene regulation by serving as a differential sink for the binding of chromatin regulators or other DNA-binding proteins, which may lead to the titration of these proteins at other genomic locations (13). The feasibility of such satellite-repeat-sink model has been demonstrated in the case of the transcription factor C/EBP alpha, which binds to satellite repeat alpha in mice (32). Moreover, analyses of enhancer-trap mutants whose expression is modulated by the Y chromosome identified a multi-megabase segment in the Y chromosome that acts as a transregulator of a lacZ reporter expression (33).…”
Section: Discussionmentioning
confidence: 99%
“…These collective findings highlight the complexity of the role of PIASy and sumoylation in the regulation of individual transcription factors. In addition, it has recently been reported that C/EBP␣ transcriptional activity may be regulated by sequestration in transcriptionally inactive pericentromeric heterochromatin (55). Since the PIASy SAP domain binds ATrich DNA present in scaffold attachment regions, also called matrix attachment regions, it is possible that subnuclear sequestration could include the binding of C/EBP␦ to AT-rich or repetitive DNA present at the nuclear periphery (31,56).…”
Section: Discussionmentioning
confidence: 99%